Combination of Nitrogen-Enriched Zeolite and Arbuscular Mycorrhizal Symbiosis to Improve Growth of Maize (Zea mays L.) - Luis G. Sarmiento-López; Arny Matos-Alegria; Mariana E. Cesario-Solis; Daniel Tapia-Maruri; Paul H. Goodwin; Carmen Quinto; Olivia Santana; Luis Cardenas (Agronomy)
Zeolite, a microporous mineral with strong ion binding, can enhance nutrient availability and growth of plants, such as maize (Zea mays L.). Arbuscular mycorrhizal (AM) symbiosis has also been shown to enhance nutrient availability and growth of plants, including maize. However, the interaction between AM symbiosis and zeolite is poorly understood. In this study, the effect on growth of maize was examined following soil treatment with N-enriched (ZN+) zeolite, which could retain 19.68% N, or N-free zeolite (ZN−), compared to N-enriched or N-free vermiculite (VN+ and VN−). There was a 2.7-times increase in the growth of maize under ZN+ treatment compared to ZN−, indicating that N could be released from zeolite for plant growth, and a 3.8-times increase with ZN+ treatment compared to VN− or VN+, indicating that zeolite was more effective than vermiculite in releasing N for plant growth. Subsequently, ZN+ and ZN− treatments were examined with non-AM (M−) and AM (M+) treatments using Rhizophagus irregularis. ZN+ M+ treatment led to higher AM colonization and development compared to M+ ZN−treatment, indicating an interaction of AM in roots with N from zeolite. PCA revealed improvements in leaf N content, photosynthetic pigments, photosynthetic performance, and secondary metabolites with M+ ZN+ treatment, which was also observed in comparison to M−ZN+ and M− ZN−treatments, further supporting the benefit of combining N from zeolite with an AM fungus. The combination of N released from N-enriched zeolite and AM symbiosis offers a promising alternative to chemical fertilizers to improve maize growth.